Перспективні енергетичні рослини роду Miscanthus Anderss., інтродуковані в Національному ботанічному саду ім. М.М. Гришка НАН України - Rakhmetov, D.B.; Scherbakova, T.O.; Rakhmetova, S.О. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
Purpose – to determine the most effective alternative sources of biofuels based on an analysis of introducents of genus Miscanthus Anderss., which are grown in M.M. Gryshko National Botanical Garden of the NAS of Ukraine, as well as the introductions potential of plants to create new varieties. Material and methods. Subject of investigation – 20 highyield species and forms of energy plants of Miscanthus genus and adaptive varieties created on their basis. Field experiments were established in accordance with the existing methods. The study of phenological phases was performed by the I.M. Beydeman method. Biometric measurements were made with reference to the H.M. Zaytseva and B.A. Dospyehov’ methods. Results. As a result of many years of introduction and breeding studies in M.M. Gryshko National Botanical Garden of the NAS of Ukraine was collected the genepool of valuable Miscanthus species, and created high-yield varieties (cv. Snihopad, cv. Veleten, cv. Huliver). We founded that the growing season of Miscanthus sacchariflorus (Мaxim.) Benth. ends in the flowering–fruiting stage, of M. sinensis Anderss. – in the flowering, and of M. × giganteus J.M. Greef et Deuter ex Hodk et Renvoize – in the phase of panicle detection (usually in the phase of shoot elongation). All plants of Miscanthus species and forms have high growth rates. Among leaf height and length characteristics have dominated plants of M. × giganteus, by stem diameter, number of internodes on the shoot, leaf blade width – samples of M. sinensis. The lowest growth rates were registered for M. sacchariflorus plants. At the end of the growing season compared to the previous period the high growth rates were registered. M. sinensis has the greatest heterogeneity of leaves (size, color, diversity, etc.) depending on the structure features of plants. The main morphological characteristics of panicle (the shape, length, width, number of branches in panicles, their size and shape, etc.) of various species and forms of Miscanthus are outlined. These factors, as important diagnostic features, were used to develop methods of expertise for differentiation, uniformity and stability of Miscanthus varieties. Plants of M. sacchariflorus have rhizomatous type of tillering, M. sinensis – tuft tillering, M. × giganteus – fluff tillering. Conclusion. As a result of many years of research, high introduction potential of Miscanthus species in Ukraine as a new high-yield energy plant is established.